Bistability in microcavities with incoherent optical or electrical excitation - Kyriienko, Oleksandr (2017)
We consider a quantum well embedded in a zero-dimensional microcavity with a subwavelength grated mirror, where the x-linearly polarized exciton mode is strongly coupled to the cavity photon, while y-polarized excitons remain in the weak-coupling regime. Under incoherent optical or electric pumping, we demonstrate polariton bistability associated with parametric scattering processes. Such bistability is useful for constructing polaritonic devices with optical or electrical incoherent pumping.